A process for calcining raw gypsum to improve the crystal structure of beta-hemihydrate gypsum

CN122647138APending Publication Date: 2026-08-28ZHAOQING BEIXIN BUILDING MATERIALS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611116110.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-27
Publication Date
2026-08-28

AI Technical Summary

Technical Problem

[0006]本发明的目的在于提供一种改善β-半水石膏晶体结构的生石膏煅烧工艺,以解决现有技术中难以在避免设备高温导致引发AⅢ过烧风险的前提下,协调β-半水石膏结晶所需温度与充分晶体生长时间的技术问题

Benefits of technology

[0027] This invention employs a three-stage gradient temperature control system. The preheating and stabilization stages are controlled at the β-hemihydrate gypsum crystal nucleation temperature, while the main phase transformation stage is controlled at the temperature promoting β-hemihydrate gypsum crystal growth. This allows the gypsum to sequentially undergo uniform nucleation, three-dimensional balanced growth, and lattice repair, ensuring sufficient heat conduction from the surface to the interior, and promoting Ca²⁺ crystal growth. + and SO4² - Sufficient ion migration and lattice defect repair result in a residual gypsum dihydrate conversion rate of ≥98%, ensuring stable product performance and good batch-to-batch consistency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122647138A_ABST
    Figure CN122647138A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of gypsum cement preparation, and discloses a calcination process for improving the crystal structure of beta-hemihydrate gypsum, which comprises the following steps: calcining raw gypsum in sequence through a preheating section, a main phase change section and a stable phase section to obtain calcined gypsum; during the calcination process in the main phase change section, a composite crystal modifier is added into the raw gypsum in real time; and the calcined gypsum is subjected to segmented cooling, grinding and homogenization to obtain modified beta-hemihydrate gypsum products. The crystal growth process is synergistically controlled by three-stage gradient temperature control and the crystal modifier, so that the beta-hemihydrate gypsum with short columnar shape, coarse crystal grains and low defects can be obtained, and the water requirement at standard consistency is significantly reduced and the strength of the hardened body is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of gypsum cementitious material preparation technology, specifically to a calcination process for raw gypsum that improves the crystal structure of β-hemihydrate gypsum. Background Technology

[0002] β-type hemihydrate gypsum (CaSO4·0.5H2O) is an air-hardening cementitious material obtained by dehydrating and calcining dihydrate gypsum (CaSO4·2H2O). It is widely used in building gypsum, plastering gypsum, self-leveling gypsum, and gypsum board. Existing preparation methods are generally one-step processes, directly calcining the dihydrate gypsum using a heating device. The drawback is that the product morphology is affected by the heating precision and heat dissipation effect of the device. This is because the heating of the device is generally not uniform; when the local temperature in the heating chamber is too high (above 200℃), soluble anhydrous gypsum (AⅢ) will be formed, leading to unstable setting time and increased water requirement for standard consistency. However, if the temperature is insufficient, the required crystallization temperature will not be reached.

[0003] When β-hemihydrate gypsum crystals lack sufficient crystallization time and temperature during rapid nucleation and growth, the crystals will appear needle-like or plate-like, with small grains and loose packing. This crystal morphology directly results in a large specific surface area and numerous lattice defects in the product, macroscopically manifested as a high standard consistency water requirement, low hardened body strength, unstable setting time, and poor volume stability.

[0004] To address the aforementioned issues, existing technology discloses a method for preparing hemihydrate gypsum (publication number: CN101708967A). This patent involves calcining dihydrate gypsum at 170–190°C for 8–12 minutes, followed by low-temperature drying and dehydration at 140–150°C for 58–65 minutes. While this process meets the drying and dehydration requirements of gypsum, it still fails to meet the crystallization process of dihydrate gypsum. Rapid calcination satisfies the temperature requirement for crystallization but not the crystallization time, while low-temperature calcination satisfies the crystallization time requirement but not the crystallization temperature. Directly increasing the temperature within this process range would be limited by the heating accuracy and heat dissipation limitations of the equipment.

[0005] It is evident that existing technologies urgently need a process that can simultaneously satisfy crystallization temperature and crystallization time, while also reducing the impact of heating equipment on the homogeneity of heating temperature. Summary of the Invention

[0006] The purpose of this invention is to provide a calcination process for raw gypsum that improves the crystal structure of β-hemihydrate gypsum, thereby solving the technical problem in the prior art of coordinating the temperature required for β-hemihydrate gypsum crystallization with sufficient crystal growth time while avoiding the risk of AⅢ overheating caused by high equipment temperature.

[0007] To solve the above-mentioned technical problems, the present invention specifically provides the following technical solution:

[0008] A process for calcining raw gypsum to improve the crystal structure of β-hemihydrate gypsum includes the following steps:

[0009] S100. Raw gypsum is sequentially calcined through a preheating section, a main phase transformation section, and a stable phase section to obtain calcined gypsum.

[0010] The temperatures of the preheating section and the stable phase section are the β-hemihydrate gypsum crystal nucleation temperature, and the temperature of the main phase transformation section is the temperature that promotes the growth of β-hemihydrate gypsum crystals.

[0011] S200. During the calcination process of the main phase transformation section, a composite crystallization agent is added to the raw gypsum in real time to inhibit the crystal from growing too fast in the length direction and promote the crystal to develop in the width direction, so as to transform the crystal from needle-shaped or long columnar to short columnar or hexagonal short columnar.

[0012] S300. The calcined gypsum is subjected to segmented cooling, grinding, and homogenization to obtain the modified β-hemihydrate gypsum product.

[0013] Further, in step S100, the temperature of the preheating section is 110-130°C, the temperature of the main phase change section is 140-160°C, and the temperature of the stable phase section is 100-120°C.

[0014] Further, in step S100, the calcination time of the preheating section is 30-40 min, the calcination time of the main phase transformation section is 60-90 min, and the calcination time of the stable phase section is 20-30 min.

[0015] Further, in step S200, the amount of the composite crystallizing agent added is 0.03% to 0.08% of the mass of the raw gypsum.

[0016] Furthermore, the composite crystallization agent is composed of an inorganic metal salt and an organic carboxylate salt in a 1:1 ratio;

[0017] The inorganic metal salt is selected from any one or more of aluminum sulfate, magnesium sulfate, and potassium aluminum sulfate;

[0018] The organic carboxylic acid salt is selected from any one or more of sodium citrate dihydrate, potassium sodium tartrate tetrahydrate, and magnesium acetate tetrahydrate.

[0019] Furthermore, the inorganic metal salt is selected from any one or more of aluminum sulfate, magnesium sulfate, and potassium aluminum sulfate;

[0020] The organic carboxylic acid salt is selected from any one or more of sodium citrate, potassium sodium tartrate, and magnesium acetate.

[0021] Further, in step S300, the segmented cooling includes the following steps:

[0022] The calcined gypsum was slowly cooled at 80–100°C for 15–25 minutes, and then allowed to cool naturally to room temperature.

[0023] Furthermore, the raw gypsum material is selected from any one or more of natural dihydrate gypsum, desulfurized gypsum, and phosphogypsum.

[0024] The present invention further provides β-hemihydrate gypsum, wherein the modified β-hemihydrate gypsum product has short columnar / prismatic crystals, an average grain size ≥2μm, and a specific surface area of ​​4~5.5m² / g.

[0025] Furthermore, the modified β-hemihydrate gypsum product has a crystal water content of 4.8% to 5.2%, a hemihydrate phase of ≥92%, an anhydrous gypsum AⅢ of ≤3%, a standard consistency water requirement of ≤60%, and a 2-hour compressive strength of ≥6.0 MPa.

[0026] Compared with the prior art, the present invention has the following advantages:

[0027] This invention employs a three-stage gradient temperature control system. The preheating and stabilization stages are controlled at the β-hemihydrate gypsum crystal nucleation temperature, while the main phase transformation stage is controlled at the temperature promoting β-hemihydrate gypsum crystal growth. This allows the gypsum to sequentially undergo uniform nucleation, three-dimensional balanced growth, and lattice repair, ensuring sufficient heat conduction from the surface to the interior, and promoting Ca²⁺ crystal growth. + and SO4² - Sufficient ion migration and lattice defect repair result in a residual gypsum dihydrate conversion rate of ≥98%, ensuring stable product performance and good batch-to-batch consistency.

[0028] This invention achieves a gradual cooling of calcined gypsum, allowing the soluble anhydrous gypsum (AⅢ) generated at high temperatures to fully reverse back into β-hemihydrate gypsum and release internal thermal stress within the crystals. As a result, the residual AⅢ content in the product is reduced from 7.2% in the traditional process to 1.8%–2.1%, thus reducing the product's water requirement.

[0029] This invention utilizes the synergistic effect of inorganic metal salts and organic carboxylate salts by adding a composite crystal transformation agent in real time during the main phase transformation stage to selectively inhibit excessively rapid growth in the length direction of crystals and promote growth in the width direction. This transforms the needle-like / flaky crystals of traditional processes into short columnar / hexagonal short columnar crystals, reduces the aspect ratio from 8:1 in traditional processes to 3-4:1, and increases the 2-hour compressive strength from 4.1 MPa in traditional processes to 6.1-6.9 MPa. Attached Figure Description

[0030] To more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings in the following description are merely exemplary, and those skilled in the art can derive other embodiments based on the provided drawings without creative effort.

[0031] Figure 1 This is a flowchart illustrating an embodiment of the present application. Detailed Implementation

[0032] To make the objectives, technical solutions, and advantages of this application clearer, the technical solutions of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0033] The dehydration process of gypsum dihydrate follows a phased mechanism: when the temperature reaches about 107℃, gypsum dihydrate begins to lose some of its water of crystallization; when the temperature rises to about 120℃, β-hemihydrate gypsum crystal nuclei are formed; crystal growth is completed in the temperature range of 160 to 180℃, and it eventually transforms into β-type hemihydrate gypsum.

[0034] Based on this, such as Figure 1 As shown, the present invention provides a calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum, comprising the following steps:

[0035] S100. Raw gypsum is calcined sequentially through a preheating section, a main phase change section, and a stable phase section to obtain calcined gypsum. The calcination equipment can be a compartment temperature-controlled continuous calcination furnace or a fluidized bed calcination device.

[0036] The temperatures of the preheating section and the stable phase section are the β-hemihydrate gypsum crystal nucleation temperature, and the temperature of the main phase transformation section is the temperature that promotes the growth of β-hemihydrate gypsum crystals.

[0037] S200. During the calcination process of the main phase transformation section, a composite crystallization agent is added to the raw gypsum in real time to inhibit the crystal from growing too fast in the length direction and promote the crystal to develop in the width direction, so as to transform the crystal from needle-shaped or long columnar to short columnar or hexagonal short columnar.

[0038] S300. The calcined gypsum is subjected to segmented cooling, grinding, and homogenization to obtain the modified β-hemihydrate gypsum product.

[0039] Processing is used to achieve gradient control and synergistic regulation of the crystal growth process of β-hemihydrate gypsum, so as to improve the crystal morphology and internal structure and obtain short columnar, coarse-grained, low-defect, and low-water-demand β-hemihydrate gypsum.

[0040] The calcination of gypsum (calcium sulfate dihydrate, CaSO4·2H2O) to produce β-hemihydrate gypsum (CaSO4·0.5H2O) requires a phase transition, which follows a staged dehydration mechanism: when the temperature reaches 100℃, water molecules begin to migrate from lattice vacancies, the gypsum dihydrate decomposes continuously, and thermal excitation dehydrates Ca²⁺. + and SO4² - Ions continuously migrate to the location of the new phase nucleus, causing the nucleus to grow and diffuse in all directions to form crystals with suitable shapes.

[0041] The calcination process disclosed in this invention requires three steps: preheating calcination, main phase transformation calcination, and stable phase calcination.

[0042] The calcination temperature in the preheating section is 110–130℃, with around 120℃ being the critical temperature node for the formation of stable crystal nuclei. The 110–130℃ range is the critical temperature range for the dehydration of dihydrate gypsum to form hemihydrate gypsum crystal nuclei, ensuring a gentle dehydration reaction and maintaining a moderate level of supersaturation of hemihydrate gypsum in the system. If the temperature is too high (e.g., directly exceeding 160℃), the supersaturation increases sharply, leading to the instantaneous formation of numerous crystal nuclei, ultimately resulting in small, defective crystals.

[0043] At the temperature disclosed in this invention, crystal nuclei are formed uniformly and slowly on or inside the surface of gypsum dihydrate crystals, providing a moderate number and uniformly distributed crystal nuclei substrate for subsequent crystal growth.

[0044] The calcination temperature of the main phase transformation section is 140–160°C. In this invention, the temperature of the main phase transformation section is set slightly higher than that of the preheating section. After thermal excitation enhancement, Ca²⁺… + and SO4² - The increased ion migration rate allows for more efficient diffusion from the reactants (the undehydrated dihydrate gypsum region) to the formed crystal nuclei. At this temperature, crystal growth tends to be more uniform in three dimensions, favoring the formation of short columnar crystals rather than needle-like or plate-like crystal morphologies. This temperature range represents the most active temperature range for hemihydrate gypsum crystal growth. If the temperature continues to rise above 160℃, the crystal growth rate becomes too rapid, potentially leading to an increase in lattice defects, increased internal stress, and even the transformation of some hemihydrate gypsum into anhydrous gypsum (AⅢ).

[0045] The role of the main phase transformation section is not to form a large number of new crystal nuclei, but to allow the crystal nuclei already formed in the preheating section to grow fully and orderly.

[0046] The temperature in the stable phase section is 100–120℃, decreasing to a level close to, and slightly lower than, that of the preheating section. After the temperature drops, the ion migration rate decreases, and crystal growth almost stops. At this point, the system enters a near-equilibrium state, which is conducive to the rearrangement of atoms / ions on the crystal surface to the lowest energy lattice positions, eliminating defects such as lattice distortion and dislocations generated during growth, and promoting ordered crystal arrangement. Simultaneously, it promotes the continued formation of new crystal nuclei and slow growth of residual dihydrate gypsum that was not fully transformed in the main phase transformation section, thereby improving the overall conversion rate.

[0047] It is worth noting that this temperature range is below the critical temperature for the transformation of hemihydrate gypsum to anhydrous gypsum (approximately 165°C), ensuring that the product remains stable in the β-hemihydrate gypsum phase region and avoiding over-firing to generate anhydrous gypsum.

[0048] In summary, the preheating stage ensures uniform nucleation of gypsum, resulting in a uniform distribution and moderate number of crystal nuclei; the main phase transformation stage ensures moderate growth of crystal nuclei in gypsum, maintaining uniform growth in all directions, avoiding the formation of elongated crystals, and keeping the crystals in a short columnar morphology; finally, the stabilization stage perfects the crystal lattice, repairs crystal defects, and improves phase purity.

[0049] The β-hemihydrate gypsum crystals obtained by the process of this invention exhibit a short columnar morphology and coarse grains. The short columnar crystals have a smaller specific surface area and fewer intergranular voids, thus significantly reducing the water requirement during mixing. The repair of lattice defects improves the structural integrity and strength of the crystals.

[0050] Further, in step S100, the calcination time of the preheating section is 30-40 min, the calcination time of the main phase transformation section is 60-90 min, and the calcination time of the stable phase section is 20-30 min.

[0051] The preheating stage serves to uniformly dehydrate and stabilize nucleation. If the preheating time is short, the gypsum interior has not yet reached thermal equilibrium, and the dehydration reaction only occurs on the surface of the particles. At this stage, the number of crystal nuclei formed is small and concentrated on the particle surface, while the interior remains dihydrated gypsum. During subsequent heating, rapid internal dehydration generates a large amount of internal stress, leading to crystal cracking or the formation of microcracks, resulting in a final product with many defects and low strength. If the holding time is long, the already formed fine crystal nuclei will undergo Ostwald ripening (small grains dissolve, large grains grow), resulting in a reduction in the number of crystal nuclei and uneven size. At the same time, some crystal nuclei may rearrange due to prolonged thermal disturbance, which actually increases the probability of lattice distortion.

[0052] By fixing the time between 30 and 40 minutes, heat is slowly conducted from the surface inwards, and the bound water in the dihydrate gypsum lattice is orderly removed. The system is in a "metastable supersaturation" state, and crystal nuclei precipitate uniformly and slowly inside the particles, providing a moderately numerous and uniformly distributed nucleus substrate for the subsequent main phase transformation stage.

[0053] The main phase transition section serves the functions of dehydration and crystal growth, a relatively slow process that facilitates ion migration. (Ca²⁺) + and SO4² - Sufficient time is allowed for diffusion and orderly arrangement from the reaction front to the crystal nucleus surface, enabling the crystal to fully develop in three dimensions and tend towards a short columnar shape. At the same time, the conversion rate of residual dihydrate gypsum is guaranteed to be ≥98%, avoiding the presence of unreacted nuclei.

[0054] If the time is too short, most of the gypsum dihydrate will not have completed the phase transformation, and the crystal morphology will still be slender and not long enough to reach a short columnar shape.

[0055] If the heating time at this temperature is too long, excessive dehydration can easily occur, causing it to transform into anhydrous gypsum (AⅢ). Even if the transformation is partially reversible after cooling, irreversible distortion and dislocations have already occurred in the crystal lattice. At the same time, it can easily lead to abnormally large grains in some areas, with an increase in impurities and voids inside the crystal, forming coarse grains that are "strong on the outside but weak on the inside," which in turn reduces mechanical properties.

[0056] The stable phase section serves to eliminate internal stress, repair lattice defects, and stabilize the phase. At this temperature, the Ca²⁺ on the crystal surface and inside... + SO4² - The water of crystallization molecules acquire slight thermal mobility, enabling them to migrate to lattice vacancies or dislocations, filling defects and bringing the crystal structure closer to its lowest energy state. Simultaneously, a very small amount of residual dihydrate gypsum that has not yet been transformed completes its final nucleation and growth during this stage, further improving phase purity.

[0057] If the time is too short, the repair effect will not be achieved; if the time is too long, it will affect production efficiency. Therefore, this time is the optimal production time.

[0058] Furthermore, in the process disclosed in this invention, a composite crystal-transforming agent is added during the calcination of the main phase transformation stage. During the main phase transformation stage, the composite crystal-transforming agent preferentially adsorbs onto the crystal surface along the length direction of the crystal nucleus, thereby effectively suppressing excessively rapid crystal growth in the length direction. When the excessively rapid growth in the length direction is effectively suppressed, the relative growth rate of the crystal in the width and thickness directions increases, resulting in lateral crystal growth. It is evident that the role of the composite crystal-transforming agent is to make the crystal growth tend towards isotropic equilibrium, ultimately transforming it from needle-like or long columnar crystals into ideal short columnar or hexagonal short columnar crystals.

[0059] The timing of adding the composite crystal transformation agent cannot be changed. The main phase transformation stage is the stage of rapid crystal growth, and the crystal transformation agent can intervene in the growth process in real time and directly, playing a role before the crystal is "set" and thus having the highest control efficiency. If added in the preheating stage, it may affect the uniform formation of crystal nuclei; if added in the stable phase stage, the crystal has already been basically set, so the effect is minimal.

[0060] Through the synergistic effect of composite crystallizing agent and three-stage gradient temperature control, ideal short columnar, coarse-grained β-hemihydrate gypsum can be obtained. The short columnar crystals have a smaller specific surface area and are more densely packed, requiring less mixing water to achieve the same fluidity. The large, complete crystals reduce structural defects, resulting in a denser and stronger gypsum stone structure after hardening.

[0061] The amount of the composite crystallizing agent added is 0.03% to 0.08% of the mass of the raw gypsum. If the amount is too low, the control effect is not obvious; if the amount is too high, the excess ions will become new impurities and defects, leading to a decrease in crystal strength. Therefore, the amount added needs to be clearly limited to between 0.03% and 0.08%.

[0062] The composite crystal-transforming agent is composed of an inorganic metal salt and an organic carboxylate salt in a 1:1 ratio. The composite crystal-transforming agent is more effective than a single crystal-transforming agent, and the different components can produce a synergistic effect. Specifically, the inorganic metal salt is selected from any one or more of aluminum sulfate, magnesium sulfate, and potassium aluminum sulfate, and the organic carboxylate salt is selected from any one or more of sodium citrate dihydrate, potassium sodium tartrate tetrahydrate, and magnesium acetate tetrahydrate.

[0063] Aluminum sulfate, magnesium sulfate, and potassium aluminum sulfate slow down the growth rate along the crystal length direction by releasing metal ions. Sodium citrate dihydrate, potassium sodium tartrate tetrahydrate, and magnesium acetate tetrahydrate assist inorganic salts to form more stable network complexes to enhance the inhibitory effect, while delaying the rehydration process of hemihydrate gypsum and ensuring product stability.

[0064] Combining inorganic metal salts with organic carboxylic acid salts can more effectively reduce the aspect ratio of crystals, making the crystallinity of crystals more perfect.

[0065] In step S300, the segmented cooling includes the following steps:

[0066] The calcined gypsum was slowly cooled at 80–100°C for 15–25 minutes, and then allowed to cool naturally to room temperature.

[0067] In calcination equipment, due to local overheating or excessive dehydration, a small amount of soluble anhydrous gypsum (AⅢ, i.e. CaSO4·εH2O, ε<0.5) will inevitably be generated. If extremely cold, the AⅢ phase will be "frozen" and preserved at high temperature and cannot be removed.

[0068] The temperature range of 80–100℃ is the window when the AⅢ phase is thermodynamically most unstable but kinetically most suitable for transformation into β-hemihydrate gypsum. Slow cooling for 15–25 minutes gives AⅢ sufficient time to absorb moisture from the environment (or trace amounts of water vapor remaining inside the gypsum) and transform back into stable β-hemihydrate gypsum, significantly improving the phase purity of the product.

[0069] At the same time, gradient cooling homogenizes the temperature of the crystal surface and interior. After the residual stress is fully released, it is naturally cooled to room temperature to avoid "supercooling phase transition" and structural damage.

[0070] The raw gypsum material is selected from any one or more of natural dihydrate gypsum, desulfurized gypsum, and phosphogypsum.

[0071] Example 1

[0072] Raw materials: Desulfurized gypsum with a grade of ≥85%, and a particle size of 0.2~0.8mm after pretreatment, with a purity of 93.5%; The calcination equipment is a compartment-controlled temperature continuous calcination furnace with a temperature control accuracy of ≤±3℃.

[0073] Calcination process: continuous compartment furnace with three-stage temperature control

[0074] Preheating section: 120℃, 35min

[0075] Main phase transformation stage: 150℃, 75min, add 0.05% composite crystal transformation agent (standard HG / T2225-2018 industrial aluminum sulfate: industrial grade sodium citrate dihydrate = 1:1)

[0076] Stable phase period: 110℃, 25min

[0077] Cooling: Slowly cool to 90℃ for 20 minutes

[0078] Test results: The crystals are short columnar with a particle size of D50 = 23-36 μm and a specific surface area of ​​4.2 m² / g; water of crystallization is 5.88%, half-aqueous phase is 89.12%, and AⅢ is 1.96%; the standard consistency water requirement is 60%, and the 2-hour compressive strength is 6.7 MPa.

[0079] Example 2

[0080] Raw material: Desulfurized gypsum with a grade of ≥85%, and a purity of 89% after pretreatment.

[0081] Calcination process: Fluidized bed three-stage temperature-controlled preheating section: 115℃, 38min

[0082] Main phase transformation stage: 155℃, 70min, with the addition of 0.06% composite crystallization agent (HG / T2680-2017 industrial magnesium sulfate: industrial standard HG / T4791-2014 potassium sodium tartrate tetrahydrate = 1:1). Stabilization stage: 105℃, 28min.

[0083] Cooling: Slowly cool to 85℃ for 22 minutes

[0084] Test results: The crystals are short columnar with a particle size of D50 = 21-35 μm and a specific surface area of ​​4.5 m² / g; the water of crystallization is 5.55%, the semi-aqueous phase is 90.43%, and the AⅢ phase is 1.92%; the standard consistency water requirement is 58%, and the 2-hour compressive strength is 6.7 MPa.

[0085] Comparative example (traditional one-step calcination)

[0086] The raw materials were the same as in Example 2, calcined at 150℃ for 60 min, without crystallizing agent or segmented temperature control. Results: The crystals were needle-like and flaky, with a particle size D50 of 15-38 μm and a specific surface area of ​​6.2 m² / g; water of crystallization was 5.64%, hemihydrate was 85.53%, and AlIII was 5.44%; the standard consistency water requirement was 66%, and the 2-hour compressive strength was 4.1 MPa.

[0087] The gypsum boards of Examples 1-2 and the comparative example were tested: the method for testing the morphology of the gypsum boards is GB / T5484-2024 "Methods for Chemical Analysis of Gypsum", the method for determining the water-to-gypsum ratio is GB / T17669.1-1999 "Standard Consistency Water Requirement for Building Gypsum", and the method for determining the 2-hour flexural and compressive strength is GB / T17669.3-1999 "Determination of Mechanical Properties of Building Gypsum".

[0088]

[0089] As can be seen from the comparison of the examples and comparative examples, the present invention, through the synergistic effect of three-stage gradient temperature control and real-time addition of composite crystallizing agent in the main phase transformation stage, combined with a segmented cooling process, can significantly improve the crystal morphology and structure of β-hemihydrate gypsum. Compared with the traditional one-step calcination process, the crystals of the product obtained by the present invention are transformed from needle-like and flaky to short columnar or hexagonal short columnar, the specific surface area is reduced by 20% to 30%, the standard consistency water requirement is reduced to below 60%, the 2-hour compressive strength is increased by more than 50%, and the content of soluble anhydrous gypsum AⅢ is controlled to within 3%, with comprehensive performance significantly superior to the prior art.

[0090] Conclusion: The calcination process of this invention can significantly improve the crystal structure and overall properties of β-hemihydrate gypsum.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and not to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. All such modifications or substitutions should be covered within the protection scope of this application, and should not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of this application. Therefore, the protection scope of this application should be determined by the protection scope of the claims.

Claims

1. A calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum, characterized in that, Includes the following steps: S100. Raw gypsum is sequentially calcined through a preheating section, a main phase transformation section, and a stable phase section to obtain calcined gypsum. The temperatures of the preheating section and the stable phase section are the β-hemihydrate gypsum crystal nucleation temperature, and the temperature of the main phase transformation section is the temperature that promotes the growth of β-hemihydrate gypsum crystals. S200. During the calcination process of the main phase transformation section, a composite crystallization agent is added to the raw gypsum in real time to inhibit the crystal from growing too fast in the length direction and promote the crystal to develop in the width direction, so as to transform the crystal from needle-shaped or long columnar to short columnar or hexagonal short columnar. S300. The calcined gypsum is subjected to segmented cooling, grinding, and homogenization to obtain the modified β-hemihydrate gypsum product.

2. The calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum according to claim 1, characterized in that, In step S100, the temperature of the preheating section is 110-130°C, the temperature of the main phase change section is 140-160°C, and the temperature of the stable phase section is 100-120°C.

3. The calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum according to claim 2, characterized in that, In step S100, the calcination time of the preheating section is 30-40 min, the calcination time of the main phase transformation section is 60-90 min, and the calcination time of the stable phase section is 20-30 min.

4. The calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum according to claim 1, characterized in that, In step S200, the amount of the composite crystallizing agent added is 0.03% to 0.08% of the mass of the raw gypsum.

5. The calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum according to claim 4, characterized in that, The composite crystallization agent is composed of inorganic metal salt and organic carboxylate salt in a 1:1 ratio. The inorganic metal salt is selected from any one or more of aluminum sulfate, magnesium sulfate, and potassium aluminum sulfate; The organic carboxylic acid salt is selected from any one or more of sodium citrate dihydrate, potassium sodium tartrate tetrahydrate, and magnesium acetate tetrahydrate.

6. The calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum according to claim 5, characterized in that, The inorganic metal salt is selected from any one or more of aluminum sulfate, magnesium sulfate, and potassium aluminum sulfate; The organic carboxylic acid salt is selected from any one or more of sodium citrate, potassium sodium tartrate, and magnesium acetate.

7. The calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum according to claim 1, characterized in that, In step S300, the segmented cooling includes the following steps: The calcined gypsum was slowly cooled at 80–100°C for 15–25 minutes, and then allowed to cool naturally to room temperature.

8. The calcination process for raw gypsum to improve the crystal structure of β-hemihydrate gypsum according to claim 1, characterized in that, The raw gypsum material is selected from any one or more of natural dihydrate gypsum, desulfurized gypsum, and phosphogypsum.

9. A β-hemihydrate gypsum prepared by the process according to any one of claims 1-8, characterized in that, The modified β-hemihydrate gypsum product has short columnar / prismatic crystals with an average grain size ≥2μm and a specific surface area of ​​4~5.5m² / g.

10. A β-hemihydrate gypsum according to claim 9, characterized in that, The modified β-hemihydrate gypsum product has a crystal water content of 4.8% to 5.2%, a hemihydrate phase of ≥92%, an anhydrous gypsum AⅢ of ≤3%, a standard consistency water requirement of ≤60%, and a 2-hour compressive strength of ≥6.0 MPa.

Citation Information

Patent Citations

  • Preparation method of semi-hydrated gypsum

    CN101708967A